The Habsburgs dynasty, culture and politics - Fichtner, Paula S. (Reaktion Books Ltd, 2014)
This incisive book is a fascinating new historical account charting one of the pivotal yet oft-overlooked foundation stories of modern Europe, the dynasty of the Habsburgs